Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to rigorously prove that given a cycle $\tau\in{S_n} $ of length $m$, then $\tau^{m} = e$ where $e$ is identity.

The funny thing is that I know why it works and understand it intuitively but when I try to prove it using the tools I have I cannot come up with something solid enough.

What I've tried so far:

  1. Tried induction : Starting with k=2 (transposition) it easy enough to show that it works then assuming that $\tau$ is of length $m$ that $\tau^{m} = e$ tried to prove that given $\tau_2$ with length $m+1$ that $\tau_2^{m+1} = e$ but didn't come up with a way to use my "induction hypothesis".
  2. We did prove that every cycle of length $m$ can be represented as $m-1$ transpositions, tried to express $\tau=\tau_1\circ \tau_2\circ \cdots \circ \tau_{k-1}$ where $\tau_1,\cdots,\tau_{k-1}$ are transpositions but no luck there too.
share|improve this question
add comment

2 Answers 2

up vote 4 down vote accepted

I think the best way to prove this would be to look at a permutation $\tau \in S_n$ as a function $\tau:\mathbb{Z}_n\to\mathbb{Z}_n$, and then a cycle of length $m$ is just a function that satisfies $\tau(a_i) = a_{(i+1 \mod m)}$ for some $\{a_0,\ldots,a_{m-1}\}$, and doesn't change any $a\notin \{a_0,\ldots,a_{m-1}\}$.

Then, $\tau^m$ is simply applying $\tau$ $m$ times, which means that $$\tau^m(a_i) = \tau^{m-1}(a_{(i+1\mod m)}) = \tau^{m-2}(a_{(i+2\mod m)}) = \ldots = a_{(i+m\mod m)} = a_i$$ for all $\{a_0,\ldots,a_{m-1}\}$, and clearly for any $a\notin \{a_0,\ldots,a_{m-1}\}$, $\tau^m(a)=a$, meaning that $\tau^m = e$.

share|improve this answer
add comment

Let $\tau=(a_0\ a_1\ \cdots\ a_{m-1})$. Then for each $i$ we have $\tau(a_i)=a_{i+1}$, where the indices are taken modulo $m$ (for example $a_m=a_0$). Hence $\tau^2(a_i)=\tau\bigl(\tau(a_i)\bigr)=\tau(a_{i+1})=a_{i+2}$. Continuing in this way we get $\tau^m(a_i)=a_{i+m}=a_i$, and so $\tau^m$ fixes the numbers $a_i$. This concludes the proof because obviously $\tau$ and all of its powers fix the numbers in $\{1,\dots,n\}\setminus\{a_1,\dots,a_m\}$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.